Ghostly evidence : exploring the paranormal - Halls, Kelly Milner, 1957- (Millbrook Press, 2014)
Examines photographs and eyewitness accounts of ghost hunters, paranormal experts, and mediums purporting to document paranormal activity. Includes a glossary, a list of additional resources, a list of places to visit, and an index.